Prenyltransferases catalyzing geranyldiphosphate formation in tomato fruit. (July 2020) - Hivert, Gal; Davidovich-Rikanati, Rachel; Bar, Einat; Sitrit, Yaron; Schaffer, Arthur; Dudareva, Natalia; Lewinsohn, Efraim
Graphical abstract: Highlights: LeGGPPS2 may provide GPP as a substrate for monoterpene biosynthesis in cultivated tomato fruit. LeGGPPS2 product distribution is influenced by the type and concentration of metal cofactors. Wild tomato relatives possess a newly recognized SlGPPS.SSU displaying limited expression in cultivated tomato fruit. SlGPPS.SSU interacts with LeGGPPS2 in vitro diverting its products to GPP formation. Expression levels of GPPS.SSU is in accordance with monoterpene accumulation in tomato fruit and the wild tomato relatives S.cheesmaniae and S. pimpinelifollium . Abstract: Monoterpenes contribute either favorably or adversely to the flavor of tomato, yet modern tomato varieties generally lack monoterpenes in their fruit. The main immediate biosynthetic precursor of monoterpenes is geranyldiphosphate (GPP), produced by the action of GPP synthases (GPPSs). Plant GPPSs are often heteromeric enzymes consisting of a non-catalytic small subunit (GPPS.SSU) and a large subunit (GPPS.LSU), the latter similar to geranylgeranyldiphosphate synthases (GGPPSs) which generate longer prenylphosphate chains. We show here that LeGGPPS2, an enzyme previously reported to support carotenoid biosynthesis, can synthesize farnesyldiphosphate (FPP) and GPP in vitro, in addition to geranylgeranyldiphosphate, depending on the assay conditions. Moreover, GPP formation is favored in vitro by the interaction of LeGGPPS2 with GPPS.SSU from either Anthirrhinum majus (AmGPPS.SSU) or from a newly discovered GPPS.SSU ortholog present in the genome of M82 tomato. SlGPPS.SSU is not expressed in M82 tomato fruit but its orthologs are expressed in fruit of wild tomato relatives, such as Solanum pimpinelifollium and S. cheesmaniae that accumulate monoterpenes.